A Framework for Nonconforming Mixed Finite Element Method for Elliptic Problems in ℝ3 - Gwanghyun Jo; J. H. Kim (Journal of Applied Mathematics)
In this paper, we suggest a new patch condition for nonconforming mixed finite elements (MFEs) on parallelepiped and provide a framework for the convergence. Also, we introduce a new family of nonconforming MFE space satisfying the new patch condition. The numerical experiments show that the new MFE shows optimal order convergence in Hdiv and L2-norm for various problems with discontinuous coefficient case.